Induced mass change technique for glucose detection in microcantilever-based sensors - Mohd Nor, Mardhiah; Bais, Badariah; Abd Aziz, Norazreen; Ab Rahim, Rosminazuin; Yeop Majlis, Burhanuddin (2012)
Microcantilever-based glucose sensor is a state-of-art sensor that has been widely investigated for biosensing applications. This work focuses on the preliminary study of correlation of the glucose reaction and the induced force on the microcantilever sensor by measuring the induced mass changes due to the glucose reaction. The induced force is then used to test the fabricated microcantilever sensor for glucose detection. Gold-coated glass slides were used as the immobilization sites for glucose oxidase enzyme. The reaction of the glucose oxidase enzyme and ß-D glucose was observed by injecting 5 mM glucose solution on 0.3 mL immobilized enzyme on three samples. The resulted mass changes, ranging from 151.87 mg to 180. 14 mg for the three samples, indicate a good correlation between the enzyme-glucose reaction and the induced mass change. The induced forces of 0.28 μN to 0.29 μN, converted from the mass changes of the glucose-enzyme reaction, is in a range of interactive force values commonly found in biochemical detection applications.